2018
DOI: 10.3390/cells7110195
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome and Expression Analyses of Bamboo Aquaporin Genes Reveal Their Functions Involved in Maintaining Diurnal Water Balance in Bamboo Shoots

Abstract: Water supply is essential for maintaining normal physiological function during the rapid growth of bamboo. Aquaporins (AQPs) play crucial roles in water transport for plant growth and development. Although 26 PeAQPs in bamboo have been reported, the aquaporin-led mechanism of maintaining diurnal water balance in bamboo shoots remains unclear. In this study, a total of 63 PeAQPs were identified, based on the updated genome of moso bamboo (Phyllostachys edulis), including 22 PePIPs, 20 PeTIPs, 17 PeNIPs, and 4 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [30][31][32]37]; however, the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo [36] and transcriptome studies [2,27,28,34] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [30][31][32]37]; however, the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo [36] and transcriptome studies [2,27,28,34] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [3032, 41], the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo[33] and transcriptome studies [2, 27, 28, 40] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian rhythm changes were positive at night and negative in the daytime shown by root pressure. Coexpression network of PeAQPs and sugar transport genes SRX2408703-SRX2408728 Sun et al, 2018 Genes involved in regulating mechanism for internode growth were identified. Genes for cellulose and lignin biosynthesis pathways, hormone biosynthesis, and signal transduction were significantly expressed in the internodes of wild and shengyin bamboo.…”
Section: Major Findings Accession Number Referencesmentioning
confidence: 99%